TANGGUNG JAWAB SOSIAL KORPORAT TERHADAP PEKERJA DALAM PANDANGAN ISLAM: Tinjauan Terhadap Permasalahan Para Pekerja Di Indonesia - Administrator, Journal (Al Mashalih - Journal of Islamic Law, 2018)
This article studies corporate social responsibility toward employees in Islamic perspective which foccussing on the issues of employees problems in Indonesia. This article is a qualitative research. A library reseaarch and a content analysis methode are used in this study. The library research is used to collect data, while the content analysis is used to analyse the data. The result of this study find that the were six problems wicth related with employees in Indonesia, i.e. : low salary; more working hours; poor relationships between workes and companies; discrimination between male and female workers; lack of health and safety guarantee; and low skill level of workers. The emergence of various problems related to this worker shows the implementation of corporate social responsibility that has not been fully implemented by the company. This is contrary to the principles of corporate social responsibility taught in Islam i.e. : engage the bisniss bassed of takwa; doing hablum minnallah (good relationship between people and God) and hablum minannas (good relationship between people and people); runing the company’s activities by applying the principles of making good, honest, trusworthy and fair dealing with workers and another stakeholder .